Background to the Creation of the Society of Pediatricians of Russia - Аlexander A. Baranov; Valery Yu. Albitsky; Stella A. Sher ("Paediatrician" Publishers LLC, 2016)
The article is devoted to the history of the Union of pediatricians of Russia. The study results of the works, charters of Petersburg and Moscow Society of Pediatricians founded in the XIX century, reports and resolutions of the first and the only pre-revolutionary congress and the next two congresses of pediatricians held in the 20s of the twentieth century are presented. The article shows the purposeful activity of prominent Russian pediatricians oriented on the creation of a professional organization aimed to develop pediatrics, reduce child mortality and improve children's health.